The The Relationship between Sleep Duration and Sedentary Behavior with the Incidence of Obesity in School-Age Children: A Literature Review - Munyati, Nessa Ishmah; Wahyudi, Chandra Tri (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Obesity is a growing public health issue among school-age children. Children with obesity are characterized by excessive accumulation of body fat. Various factors, for instance, lifestyle changes and sleep duration, can potentially increase the risk of obesity. This literature review aimed to identify the relationship between sleep duration, sedentary behavior, and obesity in school-age children. Method: In this review, journal articles published in the last five years were included. All relevant articles were obtained from several databases, including NCBI, ScienceDirect, PubMed and Google Scholar. The search strategy utilized the following keywords: “obesity”, “school-age children”, “sedentary”, and “sleep duration”. Results: A total of 255 articles were found in the initial search. These articles were subsequently screened using the PICOS framework. No more than 30 articles were eligible for inclusion. Conclusion: The results of the analysis show that sleep duration and sedentary behavior are factors that influence the incidence of obesity in school-age children.